2008
DOI: 10.1007/s11814-008-0117-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between disinfection by-products formation and characteristics of natural organic matter in raw water

Abstract: The influence of the characteristics of natural organic matter (NOM) on disinfection by-product formation was investigated for Maeri raw water, located in downstream of Nakdong river and Hoedong reservoir at Busan in Korea. The NOM was chlorinated and analyzed for trihalomethanes (THMs), 5 haloacetic acids (HAA-5) and total organic halide (TOX). Aromatic contents determined by specific UV absorbance at 254 nm (SUVA) correlated well with THMs, HAA-5 and TOX formation for the NOM in the Maeri raw water and Hoedo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
(16 reference statements)
1
24
0
2
Order By: Relevance
“…It also interferes with the disinfection process and results in toxic disinfection by-products (DBPs) such as trihalomethanes (THMs) and haloacetic acids (HAAs) (White et al 2003;Wong et al, 2007;Chow et al, 2008;Ratasuk et al, 2008;Krasner 2009;Matilainen et al, 2010 and2011). DPBs have been reported to pose harmful effects on human health (Hanson and Solomon 2004;Zhou et al, 2006;Jung andSon 2008 andWu et al, 2009). These byproducts had also been identified as a potential fetotoxin, mutagen and carcinogen as well (Ruddick et al, 1983;Reckhow et al, 1990 andBryant et al, 1992).…”
Section: Ts Tss Tdsmentioning
confidence: 99%
“…It also interferes with the disinfection process and results in toxic disinfection by-products (DBPs) such as trihalomethanes (THMs) and haloacetic acids (HAAs) (White et al 2003;Wong et al, 2007;Chow et al, 2008;Ratasuk et al, 2008;Krasner 2009;Matilainen et al, 2010 and2011). DPBs have been reported to pose harmful effects on human health (Hanson and Solomon 2004;Zhou et al, 2006;Jung andSon 2008 andWu et al, 2009). These byproducts had also been identified as a potential fetotoxin, mutagen and carcinogen as well (Ruddick et al, 1983;Reckhow et al, 1990 andBryant et al, 1992).…”
Section: Ts Tss Tdsmentioning
confidence: 99%
“…c. All SUVA values were <2.1, which indicated that the water samples primarily contained hydrophilic and low MW NOM moieties , particularly NEU fractions such as polysaccharose, amino sugar, and micromolecular organic material . The SUVA value and the operation time were negatively correlated, which resulted from the degradation of a portion of macromolecular organic material into micromolecular material by the photocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…These kinds of applications often lead to wastewater and groundwater contamination. In addition, this class of organic compounds has been also detected in drinking water as a result of tap water chlorination treatment (Jin and Yang, 2006;Jung and Son, 2008;Gurzau et al, 2010;Kadmi et al, 2014a,b). According to different studies, chlorophenols represent a public health concern due to their estrogenic, mutagenic or carcinogenic effects (Wada et al, 1999;Michalowicz and Duda, 2007;Gavrilescu, 2009).…”
Section: Introductionmentioning
confidence: 99%